Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12936-018-2466-3
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of mefloquine given as a 3-day artesunate–mefloquine in patients with acute uncomplicated Plasmodium falciparum malaria in a multidrug-resistant area along the Thai–Myanmar border

Abstract: BackgroundLow mefloquine exposure has been shown to contribute to treatment failure in patients with uncomplicated falciparum malaria following a 3-day artesunate–mefloquine combination. The present study aimed to develop a population pharmacokinetic model for mefloquine based on whole blood concentration–time profiles of this target population for further dose optimization.MethodsA total of 129 Burmese patients aged above 15 years who presented with typical symptoms of malaria and had a blood smear positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A higher dose of 25 mg/kg is finally recommended to account for the decline in mefloquine sensitivity 95 . The population PK of a 2‐day course of mefloquine (15 and 10 mg/kg on the first and second days) in artesunate‐mefloquine was also developed for optimization of mefloquine in Burmese patients with MDR P falciparum on the Thai‐Myanmar border 96 . It is critical that the artesunate dose and frequency of administration are carefully assessed and optimized in the event of emerging drug resistance and dose‐dependent toxicity (increased risk of neutropenia with a high dose of 6 mg/kg) 97,98 .…”
Section: Artemisinins and Actsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher dose of 25 mg/kg is finally recommended to account for the decline in mefloquine sensitivity 95 . The population PK of a 2‐day course of mefloquine (15 and 10 mg/kg on the first and second days) in artesunate‐mefloquine was also developed for optimization of mefloquine in Burmese patients with MDR P falciparum on the Thai‐Myanmar border 96 . It is critical that the artesunate dose and frequency of administration are carefully assessed and optimized in the event of emerging drug resistance and dose‐dependent toxicity (increased risk of neutropenia with a high dose of 6 mg/kg) 97,98 .…”
Section: Artemisinins and Actsmentioning
confidence: 99%
“…95 The population PK of a 2-day course of mefloquine (15 and 10 mg/kg on the first and second days) in artesunate-mefloquine was also developed for optimization of mefloquine in Burmese patients with MDR P falciparum on the Thai-Myanmar border. 96 It is critical that the artesunate dose and frequency of administration are carefully assessed and optimized in the event of emerging drug resistance and dose-dependent toxicity (increased risk of neutropenia with a high dose of 6 mg/kg). 97,98 Analysis of the parasite clearance time of artesunate-mefloquine from clinical trials in Thailand suggested the 2-mg/kg oral artesunate be the minimum dose that produces maximum effect, 99 but the 4-mg/kg target dose was selected for use in artesunatemefloquine to account for the marked interindividual variation in drug exposure.…”
Section: Artemisinins and Actsmentioning
confidence: 99%
“…Thailand similarly began using artesunate-mefloquine, until resistance to artemisinin and later mefloquine meant that even the adoption of a prolonged treatment regime was no longer effective [103,114]. Dihydroartemisinin-piperaquine was then introduced in 2015, but a failure rate of almost 93% in the north-eastern region of Thailand was observed in 2017, possibly due to imported cases from the Cambodian border [113].…”
Section: Drug Resistance In Malariamentioning
confidence: 99%